Determinación de la competitividad de la Cámara de la Pequeña Industria de Chimborazo, período 2021 - Margarita Valeria, Romero Guaraca (2021)
ABSTRACT This research determines the companies that integrate the Cámara de la Pequeña Industria of Chimborazo competitiveness level, period 2021, to explain the economic level competitiveness based on the IDB competitiveness map, also to establish the relationship between the strategic dimensions and the level of competitiveness. The IDB competitiveness map is a tool that let us know the competitiveness initial state and determines the areas to be perfected. A systemic competitiveness model was developed at a micro scale and 102 surveys were applied to managers of the MSMEs attached to the CAPICH. The instrument was validated by means of an exploratory factor analysis and confirmatory factor analysis. While in the analysis of reliability and internal consistency, obtained a Cronbach's alpha of 0.987. Among the main findings, it is shown that MSMEs have a medium level of competitiveness in general. According to the econometric analysis based on a multiple linear regression model the level of competitiveness was used as a dependent variable and human resources information systems and environmental management, production and operations, strategic planning, accounting and finance and marketing were used as independent variables. It concludes that the dimensions with a significant and positive correlation to a greater extent are 0.470 accounting and finance, 0.245 production and operations, 0.200 strategic planning, 0.207 human resources, information systems and environmental management. Keywords: Marketing, Environmental management, Strategic planning, Human resources, Information system. Reviewed by: MsC. Edison Damian Escudero ENGLISH PROFESSOR C.C.0601890593